2016
DOI: 10.3390/met6070152
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Recrystallization and Hot Workability of 316LN Stainless Steel

Abstract: Abstract:To identify the optimal deformation parameters for 316LN austenitic stainless steel, it is necessary to study the macroscopic deformation and the microstructural evolution behavior simultaneously in order to ascertain the relationship between the two. Isothermal uniaxial compression tests of 316LN were conducted over the temperature range of 950-1150˝C and for the strain rate range of 0.001-10 s´1 using a Gleeble-1500 thermal-mechanical simulator. The microstructural evolution during deformation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…316LN austenitic stainless steel has been chosen to manufacture heavy key structural components in nuclear power plant owing to its excellent corrosion resistance, high temperature mechanical properties, and adequate weldability (Jones, 1996;Zhang et al, 2014). In recent years, the research of 316LN steel mainly focuses on two aspects: performance and hot deformation (Anita et al, 2006;Kim et al, 2009;Schwartz et al, 2010;Kim, 2012;Mathew et al, 2012;Samantaraya et al, 2012;Duan and Liu, 2013;Zhang et al, 2013;Chen et al, 2014;Samantaray et al, 2014;Sun et al, 2016). In terms of performance, researchers mainly studied creep and fatigue behavior (Schwartz et al, 2010;Mathew et al, 2012), stress corrosion crack (Anita et al, 2006), mechanical properties (Kim, 2012) and welding characteristics (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…316LN austenitic stainless steel has been chosen to manufacture heavy key structural components in nuclear power plant owing to its excellent corrosion resistance, high temperature mechanical properties, and adequate weldability (Jones, 1996;Zhang et al, 2014). In recent years, the research of 316LN steel mainly focuses on two aspects: performance and hot deformation (Anita et al, 2006;Kim et al, 2009;Schwartz et al, 2010;Kim, 2012;Mathew et al, 2012;Samantaraya et al, 2012;Duan and Liu, 2013;Zhang et al, 2013;Chen et al, 2014;Samantaray et al, 2014;Sun et al, 2016). In terms of performance, researchers mainly studied creep and fatigue behavior (Schwartz et al, 2010;Mathew et al, 2012), stress corrosion crack (Anita et al, 2006), mechanical properties (Kim, 2012) and welding characteristics (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of performance, researchers mainly studied creep and fatigue behavior (Schwartz et al, 2010;Mathew et al, 2012), stress corrosion crack (Anita et al, 2006), mechanical properties (Kim, 2012) and welding characteristics (Kim et al, 2009). In terms of hot deformation, Duan and Liu (2013) and Zhang et al (2013) conducted researches on cracking issue of 316LN steel during hot deformation, and presented prediction models for cracking, respectively; Chen et al (2014) predicted the microstructural evolution of 316LN steel using cellular automaton method; Hot processing map of 316LN steel was built by Sun et al (2016) who discussed the hot workability of 316LN steel; Samantaraya et al (2012), Samantaray et al (2014) revealed the unbalance phenomenon between energy input and energy dissipation during hot deformation of 316LN steel.…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive equation is an important mathematical model to predict and analyze the relationship among temperature, strain rate, and flow stress in a wide hot deformation temperature range [36,37]. The dependence of flow stress to hot deformation variables can be analyzed by the well-known hyperbolic sine function [38] incorporated with the definition of the Zener-Hollomon parameter as follows:…”
Section: Establishment Of Constitutive Relationship At Peak Strainmentioning
confidence: 99%
“…Hot processing maps have been widely used to study deformation behaviors of many materials [5,16,17].Processing maps are normally constructed by overprinting power dissipation maps and instability regime maps. Processing maps are based on the dynamic materials model, the principles of which have been described earlier [18][19][20][21].…”
Section: Hot Processing Mapmentioning
confidence: 99%
“…Hot processing maps have been widely used to study deformation behaviors of many materials [5,16,17]. Processing maps are normally constructed by overprinting power dissipation maps and instability regime maps.…”
Section: Hot Processing Mapmentioning
confidence: 99%